Segmental colitis associated with diverticulosis: a clinical entity to know and to look for - Tomba, Carolina; Elli, Luca (Acta Biomedica Atenei Parmensis, 2013)
Patients with diverticulosis may develop inflammatory manifestations with segmentary involvement  of the colon (segmental colitis associated with diverticulosis, SCAD), an often underestimated clinical condition. We observed the case of a 59 year-old man who presented with abdominal pain, change in bowel habit and hematochezia. Endoscopic and histological evaluation showed features suggestive for SCAD. Medical therapy has been confirmed successful in this patient.